Caracterização de bioprodutos da pirólise de biomassa de baru (Dipteryx alata Vog) e seu potencial como coadjuvantes tecnológicos - Nemet, Yara Karla de Salles (Universidade Federal do Tocantins, 2021)
Vegetable biomass is a complex mixture consisting in particular of cellulose, hemicellulose and lignin and is of great importance as a source of renewable resources, due to the production of waste and its potential in the generation of products with high added value. In this work, the physical-chemical characterization of baru residues (crude biomass) from the endocarp and mesocarp was carried out, in order to evaluate its potential as a source of technological assistants. For this, the residues were submitted to acid hydrolysis and slow pyrolysis processes. From the hydrolysis process, a liquid rich in sugars and a solid residue (rich in lignin) were obtained, which was pyrolyzed, in the same way as crude biomass. After obtaining the biocarbons, they were activated using zinc chloride as a chemical activation reagent. The biochar samples were characterized with analytical techniques such as mid-infrared spectroscopy, thermal analysis, approximate and elementary analysis, surface analysis and carbohydrate adsorption. Bio-oils were identified and quantified through gas chromatography coupled with mass spectrometry (CG-EM). The percentage of biochar obtained was 50.30% for the mesocarp and 49.19% for the endocarp from the crude sample. For hydrolyzed sample the yield was 48.50% for the mesocarp and 47.90% for the endocarp. Low ash contents (<0.56%) were found in all biocarbons and high carbon contents (> 70%). The activated biocarbons of the crude and hydrolyzed samples of the endocarp fraction of Baru showed significantly higher values (> 600 m2 / g) for surface area when compared with commercial activated carbon. The percentage of carbohydrate adsorption found on baru coals (regardless of fraction and process) was lower than the adsorption recorded for commercial activated carbon, which is desirable in the food industries. As for the bio-oil yield, the values of 30.30% for mesocarp and 38.50% for the endocarp were obtained for the crude sample, while for the hydrolyzed sample 33.10% for the mesocarp and 37.90% to the endocarp. Among the main inputs found in bio-oil are cis-vaccenic acid (36%), n-hexacanoic acid (31%) and guaiacol (28.68%). Based on these results, it is possible to conclude that baru waste has a high application potential to provide technological adjuvants in the food industries